2014
DOI: 10.1016/j.sjbs.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

De-hairing protease production by an isolated Bacillus cereus strain AT under solid-state fermentation using cow dung: Biosynthesis and properties

Abstract: Agro-industrial residues and cow dung were used as the substrate for the production of alkaline protease by Bacillus cereus strain AT. The bacterial strain Bacillus cereus strain AT produced a high level of protease using cow dung substrate (4813 ± 62 U g(-1)). Physiological fermentation factors such as the incubation time (72 h), the pH (9), the moisture content (120%), and the inoculum level (6%) played a vital role in the enzyme bioprocess. The enzyme production improved with the supplementation of maltose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 43 publications
3
29
3
1
Order By: Relevance
“…Fresh cow dung contains unstable OMs [17] which are very poor substrate for adsorption; even it inhibits adsorption by blocking adsorption sites [18]. However, these unstable OMs were converted to stable substrate [19] following PO 4 3-adsorption with time.…”
Section: Comparison Of Phosphorus Adsorption Capacity With Timementioning
confidence: 99%
“…Fresh cow dung contains unstable OMs [17] which are very poor substrate for adsorption; even it inhibits adsorption by blocking adsorption sites [18]. However, these unstable OMs were converted to stable substrate [19] following PO 4 3-adsorption with time.…”
Section: Comparison Of Phosphorus Adsorption Capacity With Timementioning
confidence: 99%
“…Al-Khaldi and Al-Abdalall 235 Results proved that magnesium ions (Mn +2 ) was the ideal ions which activated enzyme reaction; these findings agreed with that found by Sharaf and Al-Fadel (2013) while the result contradict those of Sharaf and AlFadel (2013) and Vijayaraghavan et al (2014b) who found that calcium ions were the best. Sathyavrathan and Krithika (2014) found that Cu +2 ions was the best for this reaction.…”
Section: Results Inmentioning
confidence: 52%
“…Najafi et al (2005) and Mukesh et al (2012) explained that, alkaline enzyme hydrolyses collagen during incubation for 3 h and help in hair removing. Macedo et al (2005) could completely remove skin hair by using keratinase extracted from B. subtilis S14 after 9 h incubation, but Bholay et al (2012) proved that at 12 and 18 h, if incubated at 37°C skin hair can also be removed and this was also mentioned by Vijayaraghavan et al (2014b). Verma et al (2011) mentioned that, alkaline protease could remove the epidermal layer with hair by skin treatment after 24 h, while Prabhavathy et al (2013) stated that the enzyme could remove skin hair after 24 h, as the enzyme destroy the collagen and facilitate hair remove without any skin damage.…”
Section: Results Inmentioning
confidence: 99%
“…55 °C and alkaline pH conditions. A number of studies have indicated that the optimum production of protease enzyme occur at identical alkaline pH under different temperature conditions [39,40]. According to Hadder et al [41], protease enzyme having high temperature and alkaline pH activity make it ideal for detergent industries.…”
Section: Discussionmentioning
confidence: 99%